2019
DOI: 10.1136/sextrans-2019-054040
|View full text |Cite
|
Sign up to set email alerts
|

Chemsex-related drug use and its association with health outcomes in men who have sex with men: a cross-sectional analysis of Antidote clinic service data

Abstract: PurposeChemsex-related drug use (CDU) is an escalating public health issue among men who have sex with men (MSM), associated with significant physical, biomedical and psychosocial harm. Few interventions exist to help MSM engaging in chemsex and little data exist on which to build. This cross-sectional analysis, using data from Antidote, the UK’s only lesbian, gay, bisexual, and transgender specialist drug service, aims to remedy this paucity of data.MethodsModified Poisson regression was used to assess associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 16 publications
(29 reference statements)
2
43
0
1
Order By: Relevance
“…Psychoactive substances such as those used for SDU/chemsex adversely affect users’ capacity to perceive and respond to risks during sexual encounters, and may prompt them to engage in high-risk sexual practices [ 11 ]. Studies have consistently shown that SDU and chemsex were associated with a higher risk of condomless anal intercourse (CAI), group sex, and fisting, resulting in a higher risk of HIV and other STIs [ 3 , 8 , 12 ]. SDU/chemsex among MSM in Hong Kong may aggravate the worsening HIV epidemic in this group (6.54% of MSM were HIV-positive in 2017) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychoactive substances such as those used for SDU/chemsex adversely affect users’ capacity to perceive and respond to risks during sexual encounters, and may prompt them to engage in high-risk sexual practices [ 11 ]. Studies have consistently shown that SDU and chemsex were associated with a higher risk of condomless anal intercourse (CAI), group sex, and fisting, resulting in a higher risk of HIV and other STIs [ 3 , 8 , 12 ]. SDU/chemsex among MSM in Hong Kong may aggravate the worsening HIV epidemic in this group (6.54% of MSM were HIV-positive in 2017) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Factors associated with SDU/chemsex among MSM included those related to sociodemographics (eg, age, ethnicity, income, education level, and employment status), sexual orientation, and utilization of HIV testing and other HIV/STI prevention services [ 3 , 5 , 9 ]. Studies also showed that MSM with SDU/chemsex experience were more likely to access pre-exposure prophylaxis (PrEP) [ 10 , 12 ]. These factors were considered in this study.…”
Section: Introductionmentioning
confidence: 99%
“…In this research, we observed a minor proportion of patients who are dependent on addictive substances, something that was unknown to HIV clinicians and was not self-reported previously by patients. Chemsex-related drug use is an escalating public health issue among men who have sex with men, associated with significant physical, biomedical and psychosocial harm [ 48 ]. Generally, Chemsex is not self-reported by the patients to HIV clinicians and it is not identified as drug abuse by patients themselves.…”
Section: Discussionmentioning
confidence: 99%
“…However, current evidence is also limited, mainly due to methodological limitations, including small sample sizes and observational designs (Johnson et al, 2008). Furthermore, there is a lack of scientifically tested treatment behavioral intervention protocols for chemsex and sexual compulsivity for MSM living with HIV (Evers et al, 2020;Stevens et al, 2020).…”
Section: Behavioral Intervention: Ideas and Experiencesmentioning
confidence: 99%